Pinglu Canal Construction and Its Impact on Wildlife Habitat Connectivity: A Multi-Species Network Analysis and Ecological Restoration Strategy - Yuan Cao; Kai Su; Yongfa You; Xuebing Jiang; Chuang Li; Junjie Chen (Land)
The construction of the Pinglu Canal has significantly promoted economic development in southwestern Guangxi but it has also posed serious threats to wildlife habitat connectivity in the region. During the construction process, changes in land use types have led to habitat fragmentation, triggering a series of negative ecological effects, such as the “ecological island effect” and “edge effect”. This study uses the MaxEnt model to identify habitats for 11 wildlife species within the study area, categorized into terrestrial mammals, amphibians and reptiles, forest birds, and water birds, thereby constructing a multi-species habitat connectivity network (MHCN). Through complex network analysis, we assess habitat connectivity before and after the canal’s construction, as well as after implementing habitat optimization strategies. The results indicate that, following the completion of the Pinglu Canal, the wildlife habitat area decreased by 516.47 square kilometers, accounting for 5.79% of the total area, and the number of wildlife migration corridors decreased from 279 to 223, with a total decline of 56. Moreover, the average degree and clustering coefficient of habitat connectivity networks for various species showed a downward trend, while the average path length increased, indicating intensified habitat fragmentation and a growing threat to biodiversity in the region. In response, an ecological restoration strategy is proposed, which involves creating new habitats at key ecological “pinch points” and “barrier points,” increasing habitat area by 28.13% and the number of migration corridors by 33.41%, significantly enhancing the network’s robustness and connectivity. This research provides important references for biodiversity conservation and ecological restoration in the region.